2011
DOI: 10.3402/jom.v3i0.8396
|View full text |Cite
|
Sign up to set email alerts
|

Identification of interspecies interactions affectingPorphyromonas gingivalisvirulence phenotypes

Abstract: BackgroundPeriodontitis is recognized as a complex polymicrobial disease, however, the impact of the bacterial interactions among the 700–1,000 different species of the oral microbiota remains poorly understood. We conducted an in vitro screen for oral bacteria that mitigate selected virulence phenotypes of the important periodontal pathogen, Porphyromonas gingivalis.MethodWe isolated and identified oral anaerobic bacteria from subgingival plaque of dental patients. When cocultured with P. gingivalis W83, spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…The alveolar bone loss levels positively correlated with the severity of periodontal inflammation [29]. In our study, we could observe that all the diabetes mice exhibited alveolar bone loss and db/db mice exhibited more compared to other diabetes mice in both the infection and shame-infection groups.…”
Section: Discussionsupporting
confidence: 53%
“…The alveolar bone loss levels positively correlated with the severity of periodontal inflammation [29]. In our study, we could observe that all the diabetes mice exhibited alveolar bone loss and db/db mice exhibited more compared to other diabetes mice in both the infection and shame-infection groups.…”
Section: Discussionsupporting
confidence: 53%
“…The fact that numbers of both bacteria are decreasing in the control can be due to bacterial interactions, in this 6-species model. For example, several strains of A. naeslundii have already been observed to inhibit growth of P. gingivalis [32]. Besides a decrease in the control of P. gingivalis of P. intermedia, it was observed that the concentrations of these two bacteria in the presence of Bdellovibrio did not decrease as much as in the 2-species model, additionally the numbers of S. mitis and A. naeslundii tended to increase slightly.…”
Section: Discussionmentioning
confidence: 94%
“…P. gingivalis can coaggregate with a variety of oral bacteria, such as Fusobacterium nucleatum, Actinomyces viscosus, T. denticola, and species of Streptococcus, such as Streptococcus oralis and Streptococcus gordonii (9, 10). There are also negative interactions wherein streptococci inhibit P. gingivalis growth and protease activity (11,12). In a clinical study, Wang et al have shown that there is a negative correlation of distributions of Streptococcus cristatus and P. gingivalis in subgingival plaque (13).…”
mentioning
confidence: 99%